2014
DOI: 10.3390/e16042234
|View full text |Cite
|
Sign up to set email alerts
|

Finite-Time Chaos Suppression of Permanent Magnet Synchronous Motor Systems

Abstract: This paper considers the problem of the chaos suppression for the Permanent Magnet Synchronous Motor (PMSM) system via the finite-time control. Based on Lyapunov stability theory and the finite-time controller are developed such that the chaos behaviors of PMSM system can be suppressed. The effectiveness and accuracy of the proposed methods are shown in numerical simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…It is possible to find at least 35 works [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] in the Entropy journal that relate chaos theory in different areas; however, there are only five articles, from all areas, where reproducibility was mentioned [ 92 , 93 , 94 , 95 , 96 ]. From those aforementioned papers, only Funabashi [ 95 ] presented some slight relationship with the reproducibility of nonlinear dynamics fields.…”
Section: Related Workmentioning
confidence: 99%
“…It is possible to find at least 35 works [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] in the Entropy journal that relate chaos theory in different areas; however, there are only five articles, from all areas, where reproducibility was mentioned [ 92 , 93 , 94 , 95 , 96 ]. From those aforementioned papers, only Funabashi [ 95 ] presented some slight relationship with the reproducibility of nonlinear dynamics fields.…”
Section: Related Workmentioning
confidence: 99%
“…The objective of this paper is to design the controller such that the synchronization performance of the states and , = 1, 2, 3 between chaotic systems (6) and 7are achieved.…”
Section: System Descriptionmentioning
confidence: 99%
“…Lots of control and synchronization schemes have been represented since the discovery of chaotic impact on the motor control performance, such as finite-time control [5,6], unidirectional correlation control [7], sliding mode control [8][9][10][11], linear control [12], dynamic surface control [13,14], optimal control [15], and neural network control [16]. In [5], an adaptive finite-time control method is proposed for PMSM system to suppress the chaos behavior with parameter uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the chaotic movement of PMSM will produce irregular oscillations of torque and speed, exacerbate current noise, and worsen operation performance and may even damage the entire drive system. Therefore, research on PMSM chaos phenomenon has attracted extensive attention worldwide [2][3][4][5], and further studying on the control method of PMSM chaos is of extreme significance [6][7][8].…”
Section: Introductionmentioning
confidence: 99%